2020
DOI: 10.3390/md18120654
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols from Brown Seaweeds (Ochrophyta, Phaeophyceae): Phlorotannins in the Pursuit of Natural Alternatives to Tackle Neurodegeneration

Abstract: Globally, the burden of neurodegenerative disorders continues to rise, and their multifactorial etiology has been regarded as among the most challenging medical issues. Bioprospecting for seaweed-derived multimodal acting products has earned increasing attention in the fight against neurodegenerative conditions. Phlorotannins (phloroglucinol-based polyphenols exclusively produced by brown seaweeds) are amongst the most promising nature-sourced compounds in terms of functionality, and though research on their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 105 publications
(213 reference statements)
0
24
0
Order By: Relevance
“…A growing number of studies have indicated the bioactive potential of phlorotannins in regard to neuroprotection via antioxidant and anti‐neuroinflammatory properties, in addition to some reported anti‐aggregatory activity vs. amyloid β (Ahn et al ., 2012; Wang et al ., 2018; Lee et al ., 2019; Barbosa et al ., 2020; Shrestha et al ., 2021b). Overall, this study suggests that while diverse phlorotannins more broadly share free radical scavenging and antioxidant neuroprotective properties, not all phlorotannin classes provide discreet protection against amyloid β‐evoked neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of studies have indicated the bioactive potential of phlorotannins in regard to neuroprotection via antioxidant and anti‐neuroinflammatory properties, in addition to some reported anti‐aggregatory activity vs. amyloid β (Ahn et al ., 2012; Wang et al ., 2018; Lee et al ., 2019; Barbosa et al ., 2020; Shrestha et al ., 2021b). Overall, this study suggests that while diverse phlorotannins more broadly share free radical scavenging and antioxidant neuroprotective properties, not all phlorotannin classes provide discreet protection against amyloid β‐evoked neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These brown algae (Phaeophyta) synthesise a variety of phloroglucinol‐based polyphenols as phlorotannins. Phlorotannins have been previously demonstrated to have neuroprotective activity via various modes of action including inhibition of acetylcholinesterase, butyrylcholinesterase, monoamine oxidase and beta‐site amyloid precursor protein cleaving enzyme 1 (BACE‐1) activity (Barbosa et al ., 2020). Phlorotannins can also modulate neuronal receptors and regulate signalling pathways linked to neuroinflammation, oxidative stress and neuronal cell death (Barbosa et al ., 2020; Shrestha et al ., 2021b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine algae-derived polyphenols have been investigated for their photo protective activities. Phlorotannins, as dieckol, phloroglucinol, fucofuroeckol-A, and triphlorethol-A, isolated from marine brown algae, exhibited prominent protective effect against photo damage, induced by UVB radiation [50,51]. Thring et al determined anti-collagenase, anti-elastase, and antioxidant activities of 21 plant extracts and correlated them with the total phenolic content.…”
Section: Polyphenols: Anti-senescence Nutraceuticalsmentioning
confidence: 99%
“…In the context of multifunctional ligand therapy, marine and terrestrial organisms are a fundamental source for the discovery of new bioactive agents [ 24 , 25 , 26 , 27 , 28 ]. In the last few years, several different compounds isolated from plants and microorganisms have shown good effects for the treatment of AD and several drug candidates are in clinical trials, confirming that the use of natural compounds against AD is an active and interesting area of research [ 23 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%